2017
DOI: 10.1111/oik.04217
|View full text |Cite
|
Sign up to set email alerts
|

Host egg pigmentation protects developing parasitoids from ultraviolet radiation

Abstract: Parasites rely on their hosts not only for nutrition and reproduction, but also for protection against natural enemies and adverse climatic conditions. In host-parasite interactions, protective characteristics of both players are important to consider regarding damaging effects of environmental hazards. While ultraviolet radiation (UVR) is pervasive and harmful to organisms in general, its impact on parasite fitness remains understudied. Moreover, studies that do examine the effects of UV exposure on parasitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…In ground-nesting birds, darker eggs can sometimes have better camouflage than lighter eggs (Gómez et al, 2016;Troscianko et al, 2016), which suggests that ground-nesting birds may face trade-offs between the level of egg camouflage and dealing with high levels of solar radiation (Gómez et al, 2016;Wilson-Aggarwal et al, 2016). However, in sites where solar radiation is very high (>0.8 kW/m 2 ), lighter colors may not be advantageous because of the higher transmittance of light-colored eggshells, assuming no variation in eggshell thickness, as this increases the risk of UV radiation reaching the embryo (Abram et al, 2015;Brulez et al, 2015;Gaudreau et al, 2017;Lahti & Ardia, 2016;Maurer et al, 2015). Such high UV radiation levels are found at low latitudes, and this may be a reason for the occurrence of eggs of dark coloration at such latitudes in spite of high levels of solar radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ground-nesting birds, darker eggs can sometimes have better camouflage than lighter eggs (Gómez et al, 2016;Troscianko et al, 2016), which suggests that ground-nesting birds may face trade-offs between the level of egg camouflage and dealing with high levels of solar radiation (Gómez et al, 2016;Wilson-Aggarwal et al, 2016). However, in sites where solar radiation is very high (>0.8 kW/m 2 ), lighter colors may not be advantageous because of the higher transmittance of light-colored eggshells, assuming no variation in eggshell thickness, as this increases the risk of UV radiation reaching the embryo (Abram et al, 2015;Brulez et al, 2015;Gaudreau et al, 2017;Lahti & Ardia, 2016;Maurer et al, 2015). Such high UV radiation levels are found at low latitudes, and this may be a reason for the occurrence of eggs of dark coloration at such latitudes in spite of high levels of solar radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Because the eggs contain the DNA, harmful mutations could be inherited by the next generation (e.g., Flenley, 2011). Darker colors reduce light transmittance through eggshells, thus protecting the embryo from UV radiation (Abram et al, 2015;Brulez, Pike, & Reynolds, 2015;Gaudreau, Abram, & Brodeur, 2017;Lahti & Ardia, 2016;Maurer et al, 2015;Shafey, Ghannam, Al-Batshan, & Al-Ayed, 2004). Because the absorptance by darker colors is higher than that of lighter colors, this may result in a trade-off between the risk of egg overheating and the risk of UV radiation on embryos if ambient temperature and solar radiation are positively related (Lahti & Ardia, 2016): Darker eggshells would protect the embryo from UV radiation, but in turn would increase the risk of overheating.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the black markings absorb UV radiation while the white markings reflect it suggests that the embryos are probably protected against ionizing radiation. Podisus maculiventris (Say 1832), another stink bug, is known to have evolved selective egg pigmentation as a way to cope with UV radiation (Abram et al, 2015b) and predation (Torres-Campos et al, 2016), a trait that is recycled by its egg parasitoids (Gaudreau et al, 2017). Farnesi et al (2017) have also shown that higher levels of melanisation in mosquito eggs are inversely correlated to egg desiccation; such a function could also be served by the pigment in the Harlequin bug eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Excess exposure to water can however be just as deadly, as is the case for rainfall-related mortality in mosquito eggs (Frank and Curtis, 1977). Yet, the abiotic stressor that probably has the highest impact on egg survival is solar radiation, as prolonged exposure to sunlight can cause overheating (Hinton, 1981) and ultraviolet irradiation (Abram et al, 2015b;Gaudreau et al, 2017).…”
Section: Threats To Insect Eggsmentioning
confidence: 99%
See 1 more Smart Citation